Implications of NAD+ Metabolism in the Aging Retina and Retinal Degeneration - Martin, Pamela M.; Bartoli, Manuela; Thounaojam, Menaka C.; Jadeja, Ravirajsinh N. (Oxidative medicine and cellular longevity, 2020)
Nicotinamide adenine dinucleotide (NAD+) plays an important role in various key biological processes including energy metabolism, DNA repair, and gene expression. Accumulating clinical and experimental evidence highlights an age-dependent decline in NAD+ levels and its association with the development and progression of several age-related diseases. This supports the establishment of NAD+ as a critical regulator of aging and longevity and, relatedly, a promising therapeutic target to counter adverse events associated with the normal process of aging and/or the development and progression of age-related disease. Relative to the above, the metabolism of NAD+ has been the subject of numerous investigations in various cells, tissues, and organ systems; however, interestingly, studies of NAD+ metabolism in the retina and its relevance to the regulation of visual health and function are comparatively few. This is surprising given the critical causative impact of mitochondrial oxidative damage and bioenergetic crises on the development and progression of degenerative disease of the retina. Hence, the role of NAD+ in this tissue, normally and aging and/or disease, should not be ignored. Herein, we discuss important findings in the field of NAD+ metabolism, with particular emphasis on the importance of the NAD+ biosynthesizing enzyme NAMPT, the related metabolism of NAD+ in the retina, and the consequences of NAMPT and NAD+ deficiency or depletion in this tissue in aging and disease. We discuss also the implications of potential therapeutic strategies that augment NAD+ levels on the preservation of retinal health and function in the above conditions. The overarching goal of this review is to emphasize the importance of NAD+ metabolism in normal, aging, and/or diseased retina and, by so doing, highlight the necessity of additional clinical studies dedicated to evaluating the therapeutic utility of strategies that enhance NAD+ levels in improving vision.